PENGEMBANGAN BUKU CERITA BERGAMBAR SEBAGAI MEDIA PEMBELAJARAN TEMATIK TEMA HIDUP BERSIH DAN SEHAT KELAS II SDIT SYIFAURRAHMAH KECAMATAN PATUMBAK - Indah Ansari (JURNAL PENDIDIKAN DAN PEMBELAJARAN TERPADU (JPPT), 2022)
This development research aims to develop a picture story book as a thematic learning media on the theme of clean and healthy living that is suitable for use for learning. This research is a type of research and development using the Borg and Gall development model. The researcher carried out the Borg and Gall development model to the product revision stage. The instrument used to collect data is a questionnaire or questionnaire given to validators, namely media expert validators, material expert validators and learning expert validators. Based on the validation results from media expert validators, an average score of 3.71 was obtained in the "Good" category and provided revision notes. After the revision of the picture story book theme 4 for clean and healthy life, an average score of 4.42 was obtained in the "Very Good" category. From the results of material expert validation, an average score of 4.06 was obtained in the "Good" category and gave revision notes. After the picture story book theme 4, clean and healthy life was revised, an average score of 4.31 was obtained in the "Very Good" category. From the validation results by the linguist validator, an average score of 4.25 was obtained in the "Very Good" category and gave notes without revision and the validation results from the learning expert validators obtained an average score of 4.92 with the "Very Good" category and gave notes without revision. The average score from the assessment results of the four expert validators obtained a score of 4.35 in the "Very Good" category. It was concluded that illustrated story books with the theme of clean and healthy living with the help of the Canva application were appropriate to be used as thematic learning media for grade II SD/MI.